Laboratory Safety Practices of New Mexico Agricultural Science Teachers - Chumbley, Steven (Journal of Agricultural Systems, Technology, and Management, 2015)
To properly assess the application of safety in the agricultural mechanics laboratory, research must be conducted on what safety practices are being used, methods of teaching safety and investigation of safety equipment being used. The purpose of this study was to identify the practices of New Mexico agricultural mechanics teachers for teaching safety and managing a laboratory environment. It was found that at least 30% of all instructional time was devoted to safety. Teachers were found to be the most confident about administering first aid in an emergency. The most common safety equipment found in the agriculture laboratory were items related to eye protection and fire safety. Safety exams and safety demonstrations were the most used instructional tools for teaching safety. The highest level of importance was placed on teaching eye safety and power tool use. The least was put on making safety posters and safety inspections. Teachers felt the most prepared to teach eye safety and the use of welding systems. They felt the least prepared to teach safety laws and develop safety posters. This information is important to the future development of teacher training and in-service which should also be disseminated to campus administrators.